PELAKSANAAN KULTUM DALAM PENINGKATAN PEMAHAMAN MAKNA SHOLAT TARAWIH PADA MASYARAKAT DI MASJID JAMI’ BULUREJO JOMBANG: Implementation of Kultum in Improving Understanding of The Meaning of Tarawih Prayers In the Community at The Jami' Mosque Bulurejo Jombang - Sunardi, Sunardi; Munfarida, Isah; Kholik, Moh. (Yayasan Al-Amin Qalbu, 2024)
Tarawih prayers are one of the worship services performed during the month of Ramadan, which is an important part of Muslim religious practice. A thorough understanding of the meaning and purpose behind performing tarawih prayers is critical for Muslim communities, particularly in the context of increasing spirituality and appreciation of religion. This research aims to explore the role of implementing kultum in increasing understanding of the meaning of Tarawih prayers at the Bulurejo Jami' Mosque, Jombang, as well as its impact on the community members who participate in this activity. The method used in carrying out this service may be interactive lectures and short discussions in the Tarawih prayer congregation. The results of this service show that the implementation of kultum has a very important role in increasing understanding of the meaning of Tarawih prayers among the people of the Bulurejo Jami' Mosque. Through Kultum, worshippers can explore the theological, historical, and practical aspects of Tarawih prayers in depth. In conclusion, the implementation of the cult at the Bulurejo Jami' Mosque had a positive impact on increasing understanding of the meaning of Tarawih prayers and strengthening the community's faith and spirituality. This research recommends enhancing the quality and frequency of cultural activities and broadening community participation to enhance understanding of religion and diversity